Avaliação da sensibilidade longitudinal do questionário de qualidade de vida CCVUQ-BR em portadores de úlcera venosa crônica - Couto, Renata Cardoso [UNIFESP] (2019)
Context. Longitudinal sensitivity checks whether the score reflects changes in the patient's life due to an intervention, treatment or alteration of the clinical picture. The CCVUQ-Br was validated in the Portuguese language and needs, for a greater depth of its use, to have its longitudinal sensibility verified. At the end of this study, CCVUQ-Br will be used as an important instrument, capable of perceiving and reflecting in its score, changes in the quality of life of the patient with venous ulcer. The interest in evaluating the longitudinal sensitivity of the CCVUQ-Br arises, being relevant to answer the following research question: Is the CCVUQ-Br quality of life questionnaire longitudinally sensitive in patients with chronic venous ulcer? Objective. To evaluate the longitudinal sensitivity of the CCVUQ-Br in patients with chronic venous ulcer. Type of study. longitudinal, prospective, methodological study. Location Public and private centers for the care of patients with venous ulcer in the State of Alagoas. Sample. Individuals with chronic lower limb venous ulcer (diagnosed by the vascular surgeon), class (C6), according to the classification (CEAP), submitted to the therapeutic conduct. In this classification, venous ulcer represents the presence of skin changes with active (open) ulcer. Excluded: individuals with less than 18 years of age with associated arterial and lymphatic changes, psychiatric disorder or dementia (according to medical diagnosis), who do not speak or understand the Portuguese language, who present acute deep vein thrombosis, erysipelas, non-venous ulcers, lymphangitis and diabetes, individuals aged 60 years or older, who have cognitive impairment. Variables. Total score of the CCVUQ-Br, score on the visual analogue pain scale, score on the global scale of change, CEAP scale, ulcer size. Method. The CCVUQ-Br version was applied in a sample of 51 individuals, patients with chronic venous ulcer, recruited at random, submitted to the therapeutic treatment. After 4 weeks of therapeutic treatment, the CCVUQ-Br version was reapplied for longitudinal sensitivity testing. The numerical variables were expressed as mean and standard deviation, the categorical variables were presented in absolute and percentage frequencies, the internal consistency was analyzed by the coefficient (?) by Cronbach. Correlations of changes between, CCVUQ-Br, VAS-pain, CEAP and ulcer size, were verified by the Spearman, Pearson and Kendall tau b correlation coefficients. To evaluate the time differences between the two applications, the CCVUQ-Br, VAS- pain and ulcer size scores, the mean, median and standard deviation of the changes were calculated, and the Wilcoxon Z and T paired student tests were applied, with a significance level of 0.05. Subsequently, the size of the effect of the change and the ?² partial values were described. Results. The CCVUQ-Br presents good internal consistency (?> 0.843), decrease of the mean scores between the two moments of application and correlations of changes with the VAS-pain scale and CEAP classification. In the analysis of the changes that occurred over time, through the tests Z Wilcoxon and t paired student, values of p <0.001 were obtained. Regarding the size of the effect, one can consider that the items that presented high sensitivity were the total CCVUQ-Br score and the ulcer size, moderate sensitivity for VAS-pain and for the domains: esthetics, emotional state and social interaction and low sensitivity to domestic activities. In the partial ?² analysis, we found values ranging from 0.160 to 0.430, that is, large effect size. Conclusion. The CCVUQ-Br questionnaire, of quality of life for venous ulcer, is sensitive in longitudinal analysis when used in the Brazilian population.